Expression of midkine in normal human skin, dermatitis and neoplasms: Association with differentiation of keratinocytes. Issue 12 (4th December 2013) - Monma, Fumiko; Hozumi, Yutaka; Ikematsu, Shinya; Kawaguchi, Masakazu; Kadomatsu, Kenji; Suzuki, Tamio
Abstract Midkine is a 13‐kDa heparin‐binding growth factor. It promotes growth, survival, migration and gene expression of various target cells and play roles in many diseases. In normal adult tissues, midkine expression is highly restricted; however, midkine expression levels are high in various malignant tumors. The major biological roles of midkine can be categorized into three areas, namely, the nervous system, cancer and inflammation. Thus far, midkine has not been studied extensively in diseased human skin. We performed immunohistochemistry tests by using anti‐midkine antibodies to study the expression of midkine in normal skin and skin samples of 26 different cutaneous diseases. In addition, we investigated the expression pattern of the midkine gene in cultured keratinocytes. In normal skin, midkine expression was observed in the secretory coils of the eccrine sweat glands, outer root sheath and inner root sheath. Among the cutaneous tumors, the majority of keratinocyte‐derived neoplasms were positive for midkine. Tumors that were not derived from keratinocytes were negative for midkine. In cultured keratinocytes, the midkine gene was expressed earlier than the genes required for keratinization, for example, cytokeratin 10 and transglutaminase 1. Because midkine is expressed in the keratinized areas of normal skin, neoplasms and inflammation, it may play a role as a modulator of keratinization in the skin.